La Alianza para el Progreso y el Sistema Interamericano de Defensa (1961-1969). - RODRÍGUEZ, Froilán RAMOS; BURGOS, Pablo ESCOBAR (Humanidades: Revista de la Universidad de Montevideo)
This paper analyzes the responses of the Inter-American Defense System (IDS) in the context of the Alliance for Progress during the global Cold War of the 1960s. Methodologically, it considers historical milestones in the Americas with influence and impact on regional security. These were examined using original primary documentation from U.S. archives: The American Presidency Project, Eisenhower Library, Kennedy Library, and the OAS Archive, that were interpreted within their time and space. In particular, three different cases are studied: the Cuban Missile Crisis of 1962, the Dominican Crisis of 1965, and the achievement of the Treaty of Tlatelolco in 1967. In short, it proposes a historical interpretation of these experiences, which tested the capacity for response of hemispheric security, the relations between American states, and critical positions in moments of disagreement.